(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
This paper analyzes constitutional scopes and limits about Same-Sex marriage in the frame of Interamerican and European Human Rights Systems regarding the margin of state discretion, and how Mexican Supreme Court has adopted full recognition of that civil institution as a human right shifting on democratic principle. Perhaps, this national Supreme Court has been almost the only Court in the world that recognizes in its jurisprudence Same-Sex marriage based on equal protection clause. Therefore, it has proposed several theoretical consequences hardly to overcome. Besides that situation, it had also modified the scope of the constitutional democratic principles in México.